Team-Building Dimensions Assessment Scale: Development and Psychometric Validation of a New Tool - Fasanelli , Roberto; Foglia , Sofia; Amalfi , Giuliana; Piscitelli , Alfonso (Insight: the psychological dimensions of society, 2024)
This study aims to theoretically substantiate, develop, and validate the diagnostic tool for assessing the process and indicators of team- building in workgroups. This new psychometric scale, based on a specific theoretical model, aims to assess the functioning and potential for improvement of workgroups within organizations. The scale, with its seven dimensions of team building (such as objective, method, roles, leadership, communication, climate, and development), can make a valuable contribution to the field of team-building assessment, as it provides a comprehensive view of team dynamics. Methods. Based on a non-experimental model (specifically, a cross-sectional survey design), the research consists of three studies involving a non- probabilistic reasoned sampling strategy (N =215; N2 = 157; N3 = 279). The original instrument was initially tested on a sample of workers whose responses allowed routine statistical analyses. The instrument was subsequently modified and reduced to its more significant elements, so it was administered to the second sample of employees. Finally, after conducting a confirmatory factor analysis, the scale administered to the last sample of material industry employees. Results. Like Cronbach’s Alpha, the inter-factors and inter- items correlation indices proved significant. The validated instrument, initially consisting of 69 items, later reduced to 19, is characterized by excellent internal interdependence, which the CFA also confirmed. In the present study, the model fit indices were RMSEA = .079; SRMR = .056, CFI = .938, NFI = .907, IFI = .939, and RFI = .878. Discussion and conclusions. The findings of this study have significant practical implications. The TeBuDAS, with its comprehensive approach to team-building assessment, focusing on team cohesion and performance, offers a robust tool for organizational development. By considering the underlying culture of the organization and promoting a learning-oriented evaluation process, the TeBuDAS can guide the development strategies of the entire organization more efficiently and effectively.